Participatory Rural Appraisal (PRA) For The Development Of Safe Weaving Bamboo Production Through Community Empowerment To Improve Health And Safety Of Bamboo Weaving Craftsmen In Mojorejo, Ponorogo,East Java, Indonesia - Rindang Diannita; Mohammad Muslih; Neri Wijayanti; Umma Fatayati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
A Community service program (PKM) is a program designed for community empowerment. Mojorejo Village, Ponorogo Regency, East Java, Indonesia, is a village with bamboo producers and human resources who have expertise as woven bamboo craftsmen. The community service program aims to develop safe woven bamboo production, with the ultimate goal of increasing the income of the community in Mojorejo Village and reducing the risk of work accidents for bamboo woven craftsmen. This program uses a Participatory Rural Appraisal (PRA) approach, and identification of potential hazards, where in the program implementation it uses focus group discussions, training, socialization, counseling, and mentoring. The result of this program is an increase in the health and safety of woven bamboo craftsmen and an increase in the community's economy through product development.